Production Flexibility and the Behaviour of the Competitive Firm under Price Uncertainty - Epstein, Larry (Review of Economic Studies, 1978)
Journal Article Production Flexibility and the Behaviour of the Competitive Firm under Price Uncertainty Get access Larry Epstein Larry Epstein University of Toronto Search for other works by this author on: Oxford Academic Google Scholar The Review of Economic Studies, Volume 45, Issue 2, June 1978, Pages 251–261, https://doi.org/10.2307/2297339 Published: 01 June 1978 Article history Received: 01 May 1976 Accepted: 01 April 1977 Published: 01 June 1978